2013
DOI: 10.2147/ott.s47165
|View full text |Cite
|
Sign up to set email alerts
|

Ductal adenocarcinoma of the prostate: immunohistochemical findings and clinical significance

Abstract: IntroductionTo investigate the clinical features, diagnosis, treatment, and prognosis of ductal adenocarcinoma of the prostate.MethodsThe clinicopathological and immunohistochemical data of seven patients with ductal adenocarcinoma of the prostate were retrospectively analyzed. All patients underwent physical examination, magnetic resonance imaging (MRI), bone scan, cystoscopy, and computed tomography (CT) scan. The level of prostate-specific antigen (PSA) before and after surgery was assessed. Different prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…However, this might not be the case for some rare and special differential diagnostic considerations as for example in the discrimination of ductal prostate cancer and the enteric type of urachal adenocarcinomas, in which immunohistochemistry for prostate specific acid phosphatase (PAP) and prostate-specific antigen (PSA) (both negative in urachal adenocarcinomas and positive in ductal prostate cancer) might be useful [ 21 , 27 , 74 , 77 , 100 , 245 , 255 , 357 ].…”
Section: Biomarkers In Urachal Cancer: Immunohistochemistrymentioning
confidence: 99%
“…However, this might not be the case for some rare and special differential diagnostic considerations as for example in the discrimination of ductal prostate cancer and the enteric type of urachal adenocarcinomas, in which immunohistochemistry for prostate specific acid phosphatase (PAP) and prostate-specific antigen (PSA) (both negative in urachal adenocarcinomas and positive in ductal prostate cancer) might be useful [ 21 , 27 , 74 , 77 , 100 , 245 , 255 , 357 ].…”
Section: Biomarkers In Urachal Cancer: Immunohistochemistrymentioning
confidence: 99%
“…At present, serum prostate-specific antigen testing is the main method used to diagnose prostate cancer in clinical practice. 1 However, elevated serum prostate-specific antigen levels can also reflect pathological changes in other systems, so this test has poor specificity for prostate cancer. There is also no test presently available to predict the aggressiveness of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Sha et al. [ 16 ] sorely reminded RP could improve the outcomes of DAC with seven patients with no comparison of RT neither. Nevertheless, two of four patients receiving RP in Kan's study had biochemical recurrence 1–2 years post-operation [ 17 ], partly related to delayed diagnosis which meant DAC was more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to further investigate the outcomes of DAC treated with RP or RT. Only few studies reported the outcomes of DAC management with RP or RT with small sample sizes [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ], but failed to compare the efficacy of the two treatments. In addition, most of these studies lacked robust adjustments of confounding factors.…”
Section: Introductionmentioning
confidence: 99%